Evidence for the induction of Th2 inflammation by group 2 innate lymphoid cells in response to prostaglandin D2 and cysteinyl leukotrienes in allergic rhinitis. Issue 12 (12th August 2019) - Tojima, Ichiro; Matsumoto, Koji; Kikuoka, Hirotaka; Hara, Shiori; Yamamoto, Sayuri; Shimizu, Shino; Kouzaki, Hideaki; Shimizu, Takeshi
Abstract: Background: Group 2 innate lymphoid cells (ILC2s) play important roles in allergic inflammation. However, their roles in the pathophysiology of allergic rhinitis (AR) are poorly understood. Objective: Prevalence of ILC2s in the inferior nasal turbinate (INT) tissues and the activating mechanisms of ILC2s were examined in patients with house dust mite (HDM)‐induced AR. Methods: Eighteen patients with HDM‐induced AR and 13 control subjects were recruited. Fresh INT tissues and peripheral blood mononuclear cells (PBMCs) were analysed using flow cytometry. Nasal lavage fluids (NLF) were collected at 10 minutes after the nasal provocation test (NPT) with HDM disc, and released mediators were measured by ELISA. Sorted ILC2s were cultured and stimulated with mediators associated with AR. Results: The prevalence of ILC2s was significantly increased in nasal mucosa of patients with HDM‐induced AR, and it was positively correlated with the number of infiltrating eosinophils. ILC2s in the INT tissues expressed a prostaglandin D2 (PGD2 ) receptor, chemoattractant receptor‐homologous molecule‐expressed TH2 cells (CRTH2) and a cysteinyl leukotriene (cysLTs) receptor, CysLT1. After NPT, the number of eosinophils and concentrations of PGD2 and cysLTs were significantly increased in the NLF from AR patients. PGD2 and cysLTs significantly induced IL‐5 production from cultured PBMC‐derived ILC2s dose‐dependently. PGD2 ‐induced and cysLTs‐induced productions of IL‐5 and IL‐13 from ILC2s were completely inhibited by ramatroban, a dual CRTH2 and thromboxane receptor antagonist, and montelukast, a CysLT1 antagonist, respectively. Conclusions: PGD2 ‐CRTH2 and cysLTs‐CysLT1 axes may activate tissue‐resident ILC2s to produce Th2 cytokines, IL‐5 and IL‐13, leading to the development of allergic inflammation in AR. Abstract : The prevalence of ILC2s was increased in nasal mucosa of allergic rhinitis (AR) patients. During early‐phase responses, PGD2 and cysLTs (LTC4, LTD4, LTE4 ) may stimulate tissue‐resident ILC2s through Chemoattractant receptor‐homologous molecule expressed TH2 cells and Cysteinyl leukotriene receptor 1, leading to the development of allergic inflammation. The clinical effectiveness of ramatroban and montelukast in AR may be mediated partly through the inhibition of IL‐5/IL‐13 release from ILC2s. Abbreviations: CRTH2, chemoattractant receptor‐homologous molecule expressed on TH2 cells; CysLT1, cysteinyl leukotriene receptor, HDM, House dust mite; LT, Leukotriene; PGD2, Prostaglandin D2.